Implementasi terapi mewarnai terhadap perkembangan motorik halus pada anak - Sony Sanjaya; Eva Yunitasari; Marliyana Marliyana (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Children are individuals under the age of 18, including those still in the womb, and who are not yet married. Motor delays in children are a serious problem that can have long-term effects on their physical and mental development. Coloring therapy can help improve understanding and memory in children. Fine motor skills are necessary for daily life, involving control and coordination of the small muscles in the hands and fingers. These skills include activities such as writing, drawing, cutting with scissors, and buttoning clothes. Purpose: To determine the implementation of coloring therapy on fine motor development in children.  Method: A descriptive design using case study analysis and a case study approach to describe the results of nursing care on the implementation of coloring therapy on fine motor development in children. Results: The results of implementing coloring therapy on fine motor development in children show the results of coloring therapy intervention on fine motor development in children that have been studied. Conclusion: Children's fine motor skills are also influenced by stimulation. Interviews with parents and teachers revealed that parents never provided stimulation for their children's fine motor development at home and allowed their children to play as they pleased. Suggestion: It is hoped that this study will broaden the insight and increase the knowledge of parents and children regarding the importance of fine motor skills in children.